2021
DOI: 10.1124/dmd.120.000325
|View full text |Cite
|
Sign up to set email alerts
|

Reversible and Irreversible Inhibition of Cytochrome P450 Enzymes by Methylophiopogonanone A

Abstract: Methylophiopogonanone A (MOA), an abundant homoisoflavonoid bearing a methylenedioxyphenyl (MDP) moiety, is one of the major consitituents in the Chinese herb Ophiopogon japonicas. This work aims to assess the inhibitory potentials of MOA against cytochrome P450 enzymes, as well as to decipher the molecular mechanisms for CYP inhibition by MOA. The results showed that MOA concentration-dependently inhibited CYPs1A, 2C8, 2C9, 2C19 and 3A in human liver microsomes (HLMs) in a reversible way, with IC 50 values va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 36 publications
(45 reference statements)
0
35
0
Order By: Relevance
“…The first pathway is demethylenation (oxidative ring opening of 1,3‐benzodioxole), forming the catechol derivative (M7). This metabolite is susceptible to oxidation to produce a reactive ortho ‐quinone intermediate followed by conjugation with GSH 11 . The second pathway may be via the quinone‐methide intermediate, which is highly reactive to GSH, resulting in corresponding GSH conjugate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first pathway is demethylenation (oxidative ring opening of 1,3‐benzodioxole), forming the catechol derivative (M7). This metabolite is susceptible to oxidation to produce a reactive ortho ‐quinone intermediate followed by conjugation with GSH 11 . The second pathway may be via the quinone‐methide intermediate, which is highly reactive to GSH, resulting in corresponding GSH conjugate.…”
Section: Resultsmentioning
confidence: 99%
“…11 MOA displayed time-dependent inhibition on CYP2D6 and 2E1. 11 Chen et al demonstrated that MOA is a modulator of the transporters of OATP1B1 and OATP1B3. 12 Besides the interactions with CYPs and transporters, MOA is a naturally occurring broad-spectrum inhibitor of human UDP-glucuronosyltransferases (UGTs), especially the inhibition of UGT 1A1 (IC 50 1.23 μM).…”
Section: Introductionmentioning
confidence: 94%
“…OPA contains a methylenedioxyphenyl moiety, which is a well‐known alert functional group that can be readily bioactivated into ortho ‐quinone intermediate 11,16 . To trap the reactive intermediate, GSH was incorporated in the microsomal incubations.…”
Section: Resultsmentioning
confidence: 99%
“…Sitaxentan serves as an example 21 . In addition, these intermediates can interact with P450 enzymes, resulting in P450 enzymes inactivation, and amplify the potential of drug–drug interactions 11,16 . Therefore, further studies need to be performed to evaluate the safety of OPA.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, we reported that the methylenedioxyphenyl moiety of MOA could be activated by several cytochrome P450 enzymes (CYPs), which, in turn, inactivated CYP2E1 and CYP2D6 and thereby brought undesirable time-dependent inhibition of these two CYPs. 12 Chen et al reported that MOA increased the hepatic uptake of rosuvastatin through stimulating OATP1B1, which might result in decreased concentration in blood circulation. 13 These findings suggested that MOA could interact with some important drugmetabolizing enzymes and transporters, which, in turn, modulating the plasma exposure and treatment outcomes of western therapeutics and leading to undesirable HDIs.…”
mentioning
confidence: 99%